A lucid review of Helicobacter pylori‐induced DNA damage in gastric cancer. Issue 5 (11th July 2019) - Fu, Li; Xie, Chuan
Abstract: Helicobacter pylori ( H pylori ) is the main risk factor for gastric cancer (GC). In recent years, many studies have addressed the effects of  H pylori itself and of H pylori ‐induced chronic inflammation on DNA damage. Unrepaired or inappropriately repaired DNA damage is one possible carcinogenic mechanism. We may conclude that H pylori ‐induced DNA damage is one of the carcinogenic mechanisms of GC. In this review, we summarize the interactions between H pylori and DNA damage and the effects of H pylori ‐induced DNA damage on GC. Then, focusing on oxidative stress, we introduce the application of antioxidants in GC. At the end of this review, we discuss the outlook for further research on H pylori ‐induced DNA damage.